Screening Repurposed Antiviral Small Molecules as Antimycobacterial Compounds by a Lux-Based phoP Promoter-Reporter Platform - Li Zhu; Annie Wing-Tung Lee; Kelvin Ka-Lok Wu; Peng Gao; Kingsley King-Gee Tam; Rahim Rajwani; Galata Chala Chaburte; Timothy Ting-Leung Ng; Chloe Toi-Mei Chan; Hiu Yin Lao; Wing Cheong Yam; Richard Yi-Tsun Kao; et al. (MDPI AG, 2022)
The emergence of multidrug-resistant strains and hyper-virulent strains of Mycobacterium tuberculosis are big therapeutic challenges for tuberculosis (TB) control. Repurposing bioactive small-molecule compounds has recently become a new therapeutic approach against TB. This study aimed to identify novel anti-TB agents from a library of small-molecule compounds via a rapid screening system. A total of 320 small-molecule compounds were used to screen for their ability to suppress the expression of a key virulence gene, phop, of the M. tuberculosis complex using luminescence (lux)-based promoter-reporter platforms. The minimum inhibitory and bactericidal concentrations on drug-resistant M. tuberculosis and cytotoxicity to human macrophages were determined. RNA sequencing (RNA-seq) was conducted to determine the drug mechanisms of the selected compounds as novel antibiotics or anti-virulent agents against the M. tuberculosis complex. The results showed that six compounds displayed bactericidal activity against M. bovis BCG, of which Ebselen demonstrated the lowest cytotoxicity to macrophages and was considered as a potential antibiotic for TB. Another ten compounds did not inhibit the in vitro growth of the M. tuberculosis complex and six of them downregulated the expression of phoP/R significantly. Of these, ST-193 and ST-193 (hydrochloride) showed low cytotoxicity and were suggested to be potential anti-virulence agents for M. tuberculosis.